Mate preferences do predict attraction and choices in the early stages of mate selection - LI, Norman P. (Institutional Knowledge at Singapore Management University, 2013)
Although mate preference research has firmly established that men value physical attractiveness more than women do and women value social status more than men do, recent speed-dating studies have indicated mixed evidence (at best) for whether people’s sex-differentiated mate preferences predict actual mate choices. According to an evolutionary, mate preference priority model (Li, Bailey, Kenrick, & Linsenmeier, 2002; Li & KENRICK, 2006; Li, Valentine, & Patel, 2011), the sexes are largely similar in what they ideally like, but for long-term mates, they should differ on what they most want to avoid in early selection contexts. Following this model, we conducted experiments using online messaging and modified speed-dating platforms. Results indicate that when a mating pool includes people at the low end of social status and physical attractiveness, mate choice criteria are sex-differentiated: Men, more than women, chose mates based on physical attractiveness, whereas women, more than men, chose mates based on social status. In addition, individuals who more greatly valued social status or physical attractiveness on paper valued these traits more in their actual choices. In particular, mate choices were sex-differentiated when considering long-term relationships but not short-term ones, where both sexes shunned partners with low physical attractiveness. The findings validate a large body of mate preferences research and an evolutionary perspective on mating, and they have implications for research using speed-dating and other interactive contexts.